Early infant feeding practice and childhood obesity: the relation of breast-feeding and timing of solid food introduction with childhood obesity - VEHAPOĞLU TÜRKMEN, AYSEL; Vehapoglu, AYSEL; YAZICI, MEBRURE; Yazici, MEBRURE; NURSOY, MUSTAFA ATİLLA; DEMIR, Aysegul Dogan; ÖZKAYA, EMİN; NURSOY, Mustafa; TURKMEN, Serdar; Ozkaya, EMİN (My University, 2014)
Objective: We assessed the association of breast-feeding and timing of solid food introduction with childhood obesity.